Peran Guru dalam Mengatasi Perilaku Bullying pada Perserta Didik di Madrasah Ibtidaiyah Al Hikmah Sintang Kabupaten Sintang - Riduan, Riduan; Fadly Usman; Ashari (MGMP PAI SMP BINTAN, 2024)
Bullying is a problem that often occurs in the educational environment, including at Madrasah Ibtidaiyah. This research aims to analyze the role of teachers in overcoming bullying behavior at Madrasah Ibtidaiyah Al Hikmah, Sintang, Sintang Regency. The approach used is qualitative with a case study method. The research results show that teachers have an important role in identifying, preventing and dealing with bullying behavior through various efforts, such as providing character education, building good communication with students and parents, and creating a conducive school environment. Apart from that, cooperation between teachers, madrasah heads and the community is also a key factor in minimizing bullying behavior. This research emphasizes the importance of teacher training and awareness to understand the dynamics of bullying in order to provide appropriate intervention.